Toward Sustainable Professional Development: An Investigation of Informal Interactions Among Chinese Mathematics Teachers - Zhang, Shu; Zhao, Wenjun; Cao, Yiming (Frontiers in Psychology, 2021)
It is difficult for teachers to achieve sustainable professional development without support from other teachers. Many researchers have stated that teachers regard informal interactions in daily practice as crucial to learning from one another. In this paper, we present a study in which we investigated informal interactions between Chinese middle school mathematics teachers. Three dimensions of their interactions were identified through an analysis of semi-structured interviews. The data revealed how teachers initiate informal interactions based on shared goals, how they meet expectations of the dual roles of teaching and educational research, and how they perceive the effects of informal interactions on their teaching practices. These results contribute to a better understanding of the process of informal interactions from individual teacher perspectives. In this paper, we also discuss further implications for enhancing sustainable professional teacher development with daily practices.